The Impact of Initial Energy Reserves on Growth Hormone Resistance and Plasma Growth Hormone-Binding Protein Levels in Rainbow Trout Under Feeding and Fasting Conditions - Björnsson, Björn Thrandur; Einarsdóttir, Ingibjörg Eir; Johansson, Marcus; Gong, Ningping (Frontiers in Endocrinology, 2018)
The growth hormone (GH) – insulin-like growth factor I (IGF-I) system regulates important physiological functions in salmonid fish, including hydromineral balance, growth and metabolism. While major research efforts have been directed towards this complex endocrine system, understanding of some key aspects is lacking. The aim was to provide new insights into GH resistance and GH binding proteins (GHBPs). Fish frequently respond to catabolic conditions with elevated GH and depressed IGF-I plasma levels, a condition of acquired GH resistance. The underlying mechanisms or the functional significance of GH resistance are, however, not well understood. Although data suggest that a significant proportion of plasma GH is bound to specific GHBPs, the regulation of plasma GHBP levels as well as their role in modulating the GH-IGF-I system in fish is virtually unknown. Two in vivo studies were conducted on rainbow trout. In experiment I, fish were fasted for four weeks and then refed and sampled over 72 hours. In experiment II, two lines of fish with different muscle adiposity were sampled after 1, 2 and 4 weeks of fasting. In both studies, plasma GH, IGF-I, and GHBP levels were assessed as well as the hepatic gene expression of the growth hormone receptor isoform 2a (ghr2a). While most rainbow trout acquired GH resistance within 4-weeks of fasting, fish selected for high muscle adiposity did not. This suggests that GH resistance does not set in while fat reserves as still available for energy metabolism, and that GH resistance is permissive for protein catabolism. Plasma GHBP levels varied between 5 and 25 ng ml-1, with large fluctuations during both long-term (4 weeks) fasting and short-term (72 hours) refeeding, indicating differentiated responses depending on prior energy status of the fish. The two opposing functions of GHBPs of prolonging the biological half-life of GH while decreasing GH availability to target tissues makes the data interpretation difficult, but nutritionally-related regulatory mechanisms are suggested. The lack of correlation between hepatic ghr2a expression and plasma GHBP levels indicate that ghr2a assessment cannot be used as a proxy measure for GHBP levels, even if circulating GHBPs are derived from the GHR molecule.